Rail expansion devices and maximum dilation length in railway bridges. An experimental study. (15th February 2021) - Garcia-Sanchez, David; Sañudo, Roberto; Miranda, Marina; Tárrago, Nerea; Lenart, Stanislav
Highlights: Review of the most important Rail Expansion Devices used in railways bridges in Spain. Theoretical and field analysis of some of these Rail Expansion Devices (REDs). Analysis of the existing REDs of forty-four bridges and viaducts on the Spanish High-Speed Railway. Recommendations for design, construction and maintenance of REDs. Abstract: The use of rail expansion devices (RED) interrupts the continuity of the welded rail, causing an irregularity with the consequent reduction in comfort, but with the benefit of a significant stress reduction in the rails. Currently the Spanish Railway Administrator uses three types of RED according to their range: 300 (small RED), 600 (medium RED) and 1200 mm (large RED) for all railway structures in the network. Their use has led to the construction of railway bridges and viaducts of maximum free expansion length of just over 1100 m. Development of new high-speed railway lines increasingly demands longer structures. Thus, the maximum allowed free expansion length should be increased. This problem can be faced from two fronts: (1) the improvement of the performance of REDs by developing new designs and (2) the enhanced prediction of the bridges and viaducts real movements caused by retraction, creep and temperature. It is precisely this last approach that has been developed by analysing and reviewing some existing structures. Forty-four bridges and viaducts on the Spanish High-Speed Railway network. Specifically, the railway Lines Madrid-Barcelona, Cordoba-Malaga and Madrid-Valladolid, have been analysed to know the degree of strain of the existing REDs. With these measurements, the possibility of increasing the length of maximum free expansion of the deck has been examined and it has been proven to be possible as predicted strains were higher than the measured ones. Recommendations given have served to developed longer railway structures in Spain.